Berlin electropolis : shock, nerves, and German modernity - Killen, Andreas (University of California Press, 2006)
Focusing on the key groups of railway personnel, soldiers, & telephone operators, Killen traces the emergence in the 1880s & then later decline of the belief that modernity caused nervous illness.
Keywords: Neurasthenia -- Social aspects -- Germany -- Berlin -- History.; Mental fatigue -- Social aspects -- Germany -- Berlin -- History.; Electrotherapeutics -- Germany -- Berlin -- History.; Electrification -- Germany -- Berlin -- History.; Industrialization -- Germany -- Berlin -- Psychological aspects.; Social change -- Germany -- Berlin -- Psychological aspects.; Railroads -- Employees -- Mental health -- Germany -- Berlin.; Telephone operators -- Mental health -- Germany -- Berlin.; Soldiers -- Mental health -- Germany -- Berlin.; Psychiatry -- Germany -- Berlin -- History.; Industries.; Neurasthenia -- therapy; Neurasthenia -- history; Social Change -- history; Psychiatry -- history; Mental Fatigue -- history; Industry; History, 20th Century; History, 19th Century; Electroconvulsive Therapy -- history; Anxiety -- history; Germany; Neurasthénie -- Aspect social -- Allemagne -- Berlin -- Histoire.; Fatigue mentale -- Aspect social -- Allemagne -- Berlin -- Histoire.; Électrothérapie -- Allemagne -- Berlin -- Histoire.; Électrification -- Allemagne -- Berlin -- Histoire.; Industrialisation -- Allemagne -- Berlin -- Aspect psychologique.; Travailleurs des chemins de fer -- Santé mentale -- Allemagne -- Berlin.; Téléphonistes -- Santé mentale -- Allemagne -- Berlin.; Industrie.; Médecine -- Histoire -- 20e siècle.; Médecine -- Histoire -- 19e siècle.; HEALTH & FITNESS -- Diseases -- Nervous System (incl. Brain); HISTORY -- Europe -- General.; Industries; Electrification; Electrotherapeutics; Industrialization -- Psychological aspects; Neurasthenia -- Social aspects; Psychiatry; Social change -- Psychological aspects; Soldiers -- Mental health; Germany -- Berlin; berlin.; brain.; electricity.; europe.; factory workers.; german history.; german.; germany.; great war.; history of medicine.; history.; industrial revolution.; insanity.; labor.; lunacy.; madness.; manichean teleology.; medical community.; metropolis.; modernity.; nervous disorders.; nervous illness.; nervousness.; nonfiction.; psyche.; psychiatry.; psychology.; ptsd.; railways.; science.; shell shock.; social change.; technology.; telephone operators.; trauma.; veterans.; weimar republic.; welfare state.; women workers.; world war one.; ww1.; History